Plankton jako wskaźnik klasy czystości wody = Plankton as the water quality class indicator - Piontek, Marlena; Łuszczyńska, Katarzyna; Awińska-Więckowska, Aurelia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the diploma paper was analyzing literature on the subject of trophy and eutrophication of water reservoirs, water quality in lubuskie province and review and description of water microorganisms and their place in a lake to perform biological analysis of water quality class based on the collected plankton samples. In July, August and September different species of plankton of the lake Droszków in Lubuskie province, commune Zabor were observed.
Keywords: trofia zbiorników wodnych; eutrofizacja; plankton jako wskaźnik czystości wody; porównanie analizy fizykochemicznej i biologicznej; trophy and eurtophication of water reservoirs; biological analysis of water quality class based of plankton samples